Evidence for a raised concentration of a circulating sodium transport inhibitor in essential hypertension. - MacGregor, G A (1981)
A cytochemical technique that measures the ability of plasma to stimulate guinea-pig renal glucose-6-phosphate dehydrogenase (G6PD) activity in vitro, which is a marker of its ability to inhibit Na+-K+-adenosine-triphosphatase (Na+-K+-ATPase), was used in 19 patients with essential hypertension and 23 normotensive, healthy subjects. The ability of plasma to stimulate G6PD was significantly greater in the hypertensive patients when they were taking their normal sodium diet than in the normotensive subjects, and was significantly correlated with blood pressure. The ability of plasma to stimulate G6PD was inversely correlated with plasma renin activity in the hypertensive patients and increased with age and sodium intake in the normotensive subjects. These results support the hypothesis that essential hypertension, and also perhaps the increase in blood pressure with age in communities that consume large quantities of salt, is in part due to an increase in a circulating concentration of an inhibitor of Na+-N+-ATPase.